1988
DOI: 10.1121/1.395915
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus factors influencing the identification of voiced stop consonants by normal-hearing and hearing-impaired adults

Abstract: The effects of mild-to-moderate hearing impairment on the perceptual importance of three acoustic correlates of stop consonant place of articulation were examined. Normal-hearing and hearing-impaired adults identified a stimulus set comprising all possible combinations of the levels of three factors: formant transition type (three levels), spectral tilt type (three levels), and abruptness of frequency change (two levels). The levels of these factors correspond to those appropriate for /b/, /d/, and /g/ in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…For example, the resolution of consonant place is generally assumed to be based on spectral cues. However, Lindholm et al (1988) recently demonstrated that impaired listeners can often use temporally based cues as an aid to the resolution of consonant place. Any investigation into cue use by the hearing impaired must be careful not to make overly restrictive assumptions as to what phonemic information can be and is used by listeners.…”
Section: Cue-use By the Hearing Impairedmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the resolution of consonant place is generally assumed to be based on spectral cues. However, Lindholm et al (1988) recently demonstrated that impaired listeners can often use temporally based cues as an aid to the resolution of consonant place. Any investigation into cue use by the hearing impaired must be careful not to make overly restrictive assumptions as to what phonemic information can be and is used by listeners.…”
Section: Cue-use By the Hearing Impairedmentioning
confidence: 99%
“…The available cue set either is or is not sufficient to define the segment unambiguously. Several investigators have attempted to determine how hearing-impaired listeners use specific isolated phonemic cues (Lindholm et al, 1988;Revoile et al, 1985;Revoile et al, 1987). In general, these investigations have indicated that hearing-impaired listeners will often use the available cue set in a manner different from normally hearing listeners.…”
Section: Introductionmentioning
confidence: 99%
“…People with sensorineural loss that leaves them less able to perceive higher frequency energy typically show better perceptual performance with vowels than with consonants ͑Boothroyd, 1984; Dubno et al, 1982;Lindholm et al, 1988;Zeng and Turner, 1990͒. However, hearing-impaired listeners using cochlear implants tend to perceive consonants more accurately than vowels ͑Fu and Shannon, 1998;Teoh et al, 2003;Välimaa et al, 2002͒.…”
Section: A Evidence Of Fundamental Vowel-consonant Differencesmentioning
confidence: 95%
“…Hearing-impaired and normal-hearing adults show differential use of speech recognition cues [24][25][26][27][28][29][30][31][32][33]. In general, hearing-impaired listeners relied less on high-frequency cues preferred by normal-hearing listeners, when hearing loss compromised those cues.…”
Section: Introductionmentioning
confidence: 95%